Who Is Paying for Carbon Dioxide Removal? Designing Policy Instruments for Mobilizing Negative Emissions Technologies - Honegger, Matthias; Poralla, Matthias; Michaelowa, Axel; Ahonen, Hanna-Mari (Frontiers in Climate, 2021)
Carbon dioxide removal (CDR) poses a significant and complex public policy challenge in the long-term. Presently treated as a marginal aspect of climate policy, addressing CDR as a public good is quickly becoming essential for limiting warming to well below 2°C or 1.5°C by achieving net-zero emissions in time – including by mobilization of public and private finance. In this policy and practice review, we develop six functions jointly needed for policy mixes mobilizing CDR in a manner compatible with the Paris Agreement’s objectives. We discuss the emerging CDR financing efforts in light of these functions, and we chart a path to a meaningful long-term structuring of policies and financing instruments. CDR characteristics point to the need for up-front capital, continuous funding for scaling, and long-term operating funding streams, as well as differentiation based on permanence of storage and should influence the design of policy instruments. Transparency and early public deliberation are essential for charting a politically stable course of action on CDR, while specific policy designs are being developed in a way that ensures effectiveness, prevents rent-seeking at public expense, and allows for iterative course corrections. We propose a stepwise approach whereby various CDR approaches initially need differentiated treatment based on their differing maturity and cost through R&D pilot activity subsidies. In the longer term, CDR increasingly ought to be funded through mitigation results-oriented financing and included in broader policy instruments. We conclude that CDR needs to become a regularly-provided public service like public waste management has become over the last century.